Perlindungan Hukum Anak Sebagai Saksi dalam Sistem Peradilan Pidana di Indonesia - Irma, Ade; Putranto, Rahmat Dwi (FOCUS, 2025)
Abstract This study aims to analyze legal protection for children who act as witnesses within the criminal justice system in Indonesia. Children often face risks of trauma and intimidation during legal proceedings, which necessitates special legal protection as stipulated in Law No. 11 of 2012 on the Juvenile Criminal Justice System. This research explores the implementation of such protection and the challenges encountered in safeguarding the rights of children as witnesses. Through a qualitative approach utilizing literature review and in-depth interviews, the study reveals that despite having an adequate legal framework, its implementation faces several obstacles. These obstacles include lack of coordination among law enforcement agencies, limited resources, and social and cultural barriers that hinder optimal protection for child witnesses. Additionally, children often do not receive adequate psychological support, while child-unfriendly legal procedures exacerbate their psychological and emotional conditions. The study recommends more comprehensive policy revisions, enhanced training for law enforcement on children's rights, and strengthening of psychosocial support and infrastructure to protect children during legal processes. Effective implementation can be achieved through increased cooperation among institutions such as the police, social workers, and child protection agencies to create a system that is more responsive to the needs of child witnesses. The study emphasizes the importance of a child-centered and rehabilitative approach to ensure their physical, mental, and social well-being throughout their involvement in criminal justice proceedings.